Achieving reforms in oligarchical democracies: the role of leadership and coalitions in the Philippines - Sidel, John T. (Developmental Leadership Program, 2014)
This paper examines the role of developmental leadership in two major reforms introduced in the Philippines in 2012: the passage into law in December of excise tax reform which significantly raised taxes on cig arettes and alcohol – generally referred to as the Sin Tax Reform – an d, in July, the re-registration of voters in the Autonomous Region of Muslim Mindanao (ARMM). These reforms have a) strengthened government finances and healthcare; and b) improved the quality of elections and promoted good governance and conflict resolution in the southern Phili ppines. Key points: These reforms were not achieved exclusively throug h the executive leadership of Philippine President Benigno Aquino III, this paper argues. A broader form of developmental leadership was cri tical to their passage into legislation and their subsequent implement ation, made up of reform coalitions that incorporated elements of gove rnment, the legislature, and civil society. While these coalitions wer e diverse and flexible in their form and composition, their core stren gth came from established advocacy groups and experienced activists. T hese groups and activists used highly labour-intensive, specialized an d complex forms of mobilization. The success of these reform coalition s, it is argued, has implications for economic and governance reform i n the developing world, particularly in systems characterised by oliga rchical democracy, where competition for elected office is closely lin ked to the entrenched interests of business and industry.